RELEVANSI PEMIKIRAN TOKOH SOSIOLOGI KLASIK DALAM MENGHADAPI TANTANGAN PENDIDIKAN ISLAM - Deni Irawati; Nur Azizah; Januar Januar; Muhiddinur Kamal (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2024)
This research aims to analyze the thoughts of the pioneers of sociology on the phenomenon of Islamic education. Through a literature review, this study reveals that these figures have made significant contributions to the development of the theory of sociology of education. The research results show that educational sociology figures such as Emile Durkheim and Auguste Comte contribute to the view that religion and society are the same and that religion can be used as a means to strengthen collective consciousness. Auguste Comte contributes to promoting a more scientific approach to understanding the Qur'an and Hadith to gain a deeper understanding of the Qur'an and Hadith. Max Weber contributes to social stratification in school management, and Karl Marx with his thoughts on social equality and George Simmel with his thoughts on social interaction to be able to create a learning environment that supports positive relationships between students, teachers, and society. Therefore, by applying the perspective of these sociologists, it will provide opportunities for Islamic education to compete in the modern world.